May Functional Imaging be Helpful for Behavioral Assessment in Children? Regions of Motor and Associative Cortico-Subcortical Circuits Can be Differentiated by Laterality and Rostrality - August, Julia M.; Rothenberger, Aribert; Baudewig, Juergen; Roessner, Veit; Dechent, Peter (Frontiers in Human Neuroscience, 2015)
Background: Cortico-subcortical circuits are organized into the sensorimotor, associative and limbic loop. These neuronal preconditions play an important role regarding the understanding and treatment of behavioral problems in children. Differencing evidence argues for a lateralized organization of the sensorimotor loop and a bilateral (i.e. non-lateralized) organization of the associative loop. However, a firm behavioral-neurobiological distinction of these circuits has been difficult, specifically in children. Objectives: Thus, the aim was a comprehensive functional visualization and differentiation of the sensorimotor and the associative circuit during childhood. As a new approach, laterality and rostrality features were used to distinguish between the two circuits within one single motor task. Methods: 24 healthy boys performed self-paced index finger tapping with each hand separately during functional magnetic resonance imaging at 3 Tesla. Results: A contrast analysis for left against right hand movement revealed lateralized activation in typical sensorimotor regions such as primary sensorimotor cortex, caudal supplementary motor area (SMA), caudal putamen and thalamus. A conjunction analysis confirmed bilateral involvement of known associative regions including pre-SMA, rostral SMA and rostral putamen. Conclusion: A functional visualization of two distinct corticostriatal circuits is provided in childhood. Both, the sensorimotor and associative circuit may be discriminated by their laterality characteristics already in minors. Additionally, the results support the concept of a modified functional subdivision of the SMA in a rostral (associative) and caudal (motor) part. A further development of this approach might help to nurture behavioral assessment and neurofeedback training in child mental health.